Digital inclusion and health literacy: the education experience in times of Covid-19 Pandemic (Research, Society and Development, 2022)
The fast social transformations triggered by Information and Communication Technologies (ICTs) and by the Covid-19 pandemic brought a challenge in the field of education and health. The question whether access to ICTs is increasing (favoring) social inequalities has become more pressing than ever in the face of the Covid-19 pandemic. How to reduce the digital divide and misinformation in health is the question that this article seeks to answer. Thus, we describe an educational experience in digital literacy and health literacy during the Covid-19 pandemic through remote teaching-learning strategies using audiovisual resources and dialogic workshops with low-income residents of a large urban center in Brazil. The methodology used in the research is qualitative with the use of assessment for students and teachers. As a result of the workshops, it was possible to observe positive results that enabled the dissemination of knowledge for digital and social inclusion, in addition to health promotion and citizen empowerment.